Comparison of the Outcome and Efficacy of Single-Layer versus Dual-Layer Mesh Stent among Carotid Stenosis Patients Attending a Tertiary Care Setting—A Prospective Observational Study - Reddy, Vemireddy Pradeep Kumar; Mulimani, Navin M. (Journal of Clinical Interventional Radiology ISVIR, 2022)
The effect of stent design whether single-layer or double-layer on long-term durability of carotid artery stenting (CAS) is unknown. The aim of this article was to compare the clinical outcome and efficacy of single-layer versus dual-layer mesh stent for CAS among carotid stenosis patients. A prospective observational study was conducted among 41 consecutive patients, who underwent CAS procedures between November 2019 and November 2021. Procedural data and outcomes for patients treated with the single-layer stent (n = 19patients) and double-layer stent (n = 22) were compared. Procedural efficacy and complications were considered as primary outcome variable. SPSS version 22 was used for statistical analysis. Mean age of study population in dual-layer stents group was 63.86 ± 11.08 years and it was 61.47 ± 8.26 years in single-layer stent group. There was no statistically significant difference between two groups with age, stenosis, side of stenosis, prestenting angioplasty, and poststenting angioplasty (p-value >0.05). Out of 22 participants with dual-layer stent, only one (4.5%) participant experienced five episodes of transient ischemic attack in last 1 month. Both clinical and associated complaints were more in dual-layer group compared with single layer. One (5.26%) participant in single-layer group had reclusion/restenosis at 30 days. Majority in single-(57.8%) and double-layer (63.64%) stents group showed modified Rankin Scale score of 0. Restenosis after CAS occurred less frequently in patients treated with double-layer mesh when compared with single-layer stent. However, both stents were equally effective at preventing peri procedural complications.
Keywords: carotid artery; ischemic; stenosis; stroke; cardiovascular diseases